Examining the Implications of Climate Change and Adaptation Technologies on the Livelihood of Cocoa Farmers in Offinso Municipalities, Ghanas - Megbetor, Elias; Boateng, Solomon (Journal of Environmental Science and Economics, 2023)
Cocoa is highly sensitive to uncertainties in temperature and precipitation and is projected to be challenged by climate variability. This study examined the implications of climate change on the livelihood of cocoa farmers, and the adaptation technologies adopted to mitigate the impacts in the Offinso Municipalities. 210 cocoa farmers participated in the study, out of which 180 were selected randomly from the list of Kuapa Kokoo company. These people were interviewed with the help of questionnaires. The rest 30 were selected for focus group discussions held in two different communities. The study found deforestation, land degradation, and felling of trees for lumber and domestic fuel as the main causes of climate change. The socio-economic impacts were a reduction in crop yield and income, food insecurity, poor access to healthcare, poor water quality, drying up of streams, and reduction in labour supply. A positive revelation was that the farmers have realized a gradual increase in yield in the past three (3) years due to innovative measures adopted. Such innovations include agroforestry, good agricultural practices, crop diversification, frequent spraying, fertilizer application, adoption of hybrid varieties, and creation of fire belts. As a way of minimizing financial constraints, poor irrigation facilities, inadequate seed supply, and reduction in labour supply; the farmers receive some support from farmer organizations, the government, and cocoa companies. The study recommends that government institutions commit to the enforcement of laws on deforestation and illegal mining, ensure an effective supply of cocoa inputs, and promote adaptation measures in building farmer resilience in the study area.